Comparison of Inpatient Standard-of-Care to Outpatient Oritavancin Therapy for Patients With Acute Uncomplicated Cellulitis. (February 2023) - Williams, Brandy; Muklewicz, Justin; Steuber, Taylor D.; Williams, April; Edwards, Jonathan
Background: Shifting inpatient antibiotic treatment to outpatient parenteral antimicrobial therapy may minimize treatment for acute bacterial skin and skin structure infections, including cellulitis. The purpose of this evaluation was to compare 30-day hospital readmission or admission due to cellulitis and economic outcomes of inpatient standard-of-care (SoC) management of acute uncomplicated cellulitis to outpatient oritavancin therapy. Methods: This retrospective, observational cohort study was conducted at a 941-bed community teaching hospital. Adult patients 18 years and older treated for acute uncomplicated cellulitis between February 2015 to December 2018 were eligible for inclusion. Information was obtained from hospital and billing department records. Patients were assigned to either inpatient SoC or outpatient oritavancin cohorts for comparison. Results: 1, 549 patients were included in the study (1, 348 in the inpatient SoC cohort and 201 in the outpatient oritavancin cohort). The average length of stay for patients admitted was 3.6 ± 1.5 days. The primary outcome of 30-day hospital readmission or admission due to cellulitis occurred in 49/1348 (3.6%) patients in the inpatient SoC cohort versus 1/201 (0.5%) in the outpatient oritavancin cohort (p = 0.02). The difference between costs and reimbursement was improved in the outpatient oritavancin group (p < 0.001). Conclusion: Outpatient oritavancin for acute uncomplicated cellulitis was associated with reduction in 30-day hospital readmissions or admissions compared to inpatient SoC. Beneficial economic outcomes for the outpatient oritavancin cohort were observed. Additional studies are required to confirm these findings.